Structural Capacity and Seismic Responses Evaluation of Low-Rise Buildings by Implementing Building Information Modeling (BIM) Framework - Lumondang, Amanda; Pradana, Erik Wahyu; Sangadji, Senot (Universitas Negeri Yogyakarta, 2022)
Currently, BIM has been widely applied in structural design and construction management work. However, there has not been much BIM implementation in evaluating existing structures. Thus, BIM was implemented in this study to evaluate the structural capacity and seismic responses of low-rise buildings due to earthquake loads. The case study was conducted on the Pakubuwono X Mosque building, designed in 2017 based on SNI 2847:2013, SNI 1726:2012, and SNI 1727:2013. This research was carried out numerically by involving the interconnection of Autodesk Revit and Autodesk Robot SAP software, which worked within the BIM framework. The structural model of the Pakubuwono X Mosque building was developed using Autodesk Revit, which was connected to Autodesk Robot SAP for analysis and structural design processes. Furthermore, the design products of Autodesk Robot SAP are reconnected with Autodesk Revit to be integrated with architectural and MEP (mechanical, electrical, and plumbing) design products. In this study, the structural capacity evaluation was carried out on the floor slabs, beams, and columns. Furthermore, the seismic response in the form of modal participation mass ratio, fundamental period, base shear, and story drift are also reviewed in this study. In conclusion, all structural elements (floor slabs, beams, and columns) are adequate to support the design load as indicated by the demand-capacity ratio (D/C Ratio), which is less than 1.0. Furthermore, all parameters of seismic response reviewed in this research comply with the requirements set out in SNI 1726:2012.